2009
DOI: 10.1007/s11187-009-9185-7
|View full text |Cite
|
Sign up to set email alerts
|

Innovation success of non-R&D-performers: substituting technology by management in SMEs

Abstract: Innovation success, R&D, Innovation management, SMEs, L25, L26, O31, O32, O38, O47,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
1
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(142 citation statements)
references
References 62 publications
7
123
1
11
Order By: Relevance
“…This result indicates the importance of marketing innovation in the retail sector and is consistent with Bhaskaran (2006) and Rammer et al (2009), who note that small and medium enterprises, especially those An empirical approach to marketing innovation in small and medium retailers: an application to the Spanish sector in low-and mid-tech industries, may be more willing to engage in marketing innovation, which can be less costly than technological innovation.…”
Section: Discussionsupporting
confidence: 84%
“…This result indicates the importance of marketing innovation in the retail sector and is consistent with Bhaskaran (2006) and Rammer et al (2009), who note that small and medium enterprises, especially those An empirical approach to marketing innovation in small and medium retailers: an application to the Spanish sector in low-and mid-tech industries, may be more willing to engage in marketing innovation, which can be less costly than technological innovation.…”
Section: Discussionsupporting
confidence: 84%
“…Rammer, Czarnitzki and Spielkamp (2009) showed that 57% of small enterprises considered innovative use external sources of knowledge. Gassmann et al (2010) showed that small companies can adopt the open innovation model as a business model.…”
Section: Operation Of Small Companies In the Market: Challenges And Omentioning
confidence: 99%
“…If these considerations inform us about the mechanisms at place, they only focus on the second step of the innovation process, taking technical success as given. Other studies concerned with the latter have put forward the role of human resources management (Rammer et al 2009) and labour skills (Leiponen 2005) as complements to R&D to ensure innovation success. These findings provide empirical support to Cohen and Levinthal (1989) and Dosi et al (1995): by enhancing learning, R&D expenses develop competitive advantages (Zahra and George 2002) and have a cumulative effect on firm performance.…”
Section: Theoretical Roots and Previous Empirical Evidencementioning
confidence: 99%
“…Hall et al (2008) have the same approach: not excluding the firms with R&D equal to zero (zero R&D employees, in this case) and using a dummy variable equal to 1 when firms do not perform R&D. Cohen and Levinthal (1989) perform two separate analyses, respectively, for the whole sample and for the subsample of firms with positive R&D. Brouwer et al (1993), Leiponen (2005), Greenhalgh et al (2001), Rammer et al (2009), Stam andWennberg (2009), Hölzl (2009) and Hölzl and Friesenbichler (2010) keep the zero-R&D observations in the analysis. The other innovation studies cited in this section do not employ any variable corresponding solely to R&D.…”
Section: Theoretical Roots and Previous Empirical Evidencementioning
confidence: 99%